Intergenerational Differences in Current Contraceptive Use among Married Women in Uganda. (7th August 2013) - Wablembo, Sarah M.; Doctor, Henry V.
Abstract : We analyze variations in contraceptive use and age cohort effects of women born from 1957 to 1991 based on the hypothesis that individuals born at different time periods experience different socio-economic circumstances. Differential exposure to socioeconomic circumstances may influence women's attitudes and behavior towards critical life issues such as contraceptive use. We use data from the 2006 Uganda Demographic and Health Survey by limiting the analysis to 5, 362 women who were currently married (or cohabiting) at the time of the survey. Logistic regression analyses show a higher likelihood of contraceptive use among older cohorts than younger cohorts. These results call for interventions that target young women to reduce fertility and reproductive health challenges associated with too many or too closely spaced births. Although variations in age cohorts are critical in influencing current contraceptive use, other factors such as wealth status, education level, and place of residence are equally important. Thus, interventions that focused on selected regions (e.g., the North and the West Nile), rural communities, and efforts to increase literacy levels will accelerate uptake of contraception and improve maternal and child health.